Composition, formation, and regulation of the cytosolic c-ring, a dynamic component of the type III secretion injectisome. - Andreas Diepold; Mikhail Kudryashev; Nicolas J Delalez; Richard M Berry; Judith P Armitage (PLoS Biology)
Many gram-negative pathogens employ a type III secretion injectisome to translocate effector proteins into eukaryotic host cells. While the structure of the distal "needle complex" is well documented, the composition and role of the functionally important cytosolic complex remain less well understood. Using functional fluorescent fusions, we found that the C-ring, an essential and conserved cytosolic component of the system, is composed of ~22 copies of SctQ (YscQ in Yersinia enterocolitica), which require the presence of YscQC, the product of an internal translation initiation site in yscQ, for their cooperative assembly. Photoactivated localization microscopy (PALM) reveals that in vivo, YscQ is present in both a free-moving cytosolic and a stable injectisome-bound state. Notably, fluorescence recovery after photobleaching (FRAP) shows that YscQ exchanges between the injectisome and the cytosol, with a t½ of 68 ± 8 seconds when injectisomes are secreting. In contrast, the secretin SctC (YscC) and the major export apparatus component SctV (YscV) display minimal exchange. Under non-secreting conditions, the exchange rate of YscQ is reduced to t½ = 134 ± 16 seconds, revealing a correlation between C-ring exchange and injectisome activity, which indicates a possible role for C-ring stability in regulation of type III secretion. The stabilization of the C-ring depends on the presence of the functional ATPase SctN (YscN). These data provide new insights into the formation and composition of the injectisome and present a novel aspect of type III secretion, the exchange of C-ring subunits, which is regulated with respect to secretion.